Development of a Broadly Applicable Assay for Measurement of Glycan-Directed Enzymatic Activity. (October 2018) - Bresciani, Alberto; Cecchetti, Ottavia; Missineo, Antonino; Pacifici, Pier Giorgio; Tomei, Licia; Rodems, Steven
Glycosylation is a key posttranslational modification that tags protein to membranes, organelles, secretory pathways, and degradation. Aberrant protein glycosylation is present both in acquired diseases, such as cancer and neurodegeneration, and in congenital disorders of glycosylation (CDGs). Consequently, the ability to interrogate the activity of enzymes that can modify protein glycan moieties is key for drug discovery projects aimed at finding modulators of these enzymes. To date, low-throughput technologies such as SDS-PAGE and mass spectrometry have been used, which are not suitable for compound screening in drug discovery. In the present work, a broadly applicable time-resolved fluorescence resonance energy transfer (TR-FRET) assay was developed that can determine the activity of endoglycosidase enzymes in high-throughput formats. The assay was validated using PNGaseF and EndoH as tool deglycosylases. Even though the current setup is based on the recognition of glycans that bind concanavalin A (ConA), the assay concept can be adapted to glycans that bind other lectins.